Closing the funding gap: The New Collective Quantified Goal (NCQG) for transformational change in agrifood sector. CGIAR Issue Brief Series for Informing COP 29 | Number 3 - Chilambe, Pedro; Jalang'o Anyango, Dorcas; Kinyua, Ivy; Akoko, T.; Smith, G.; Stapleton, James (CGIAR Climate Change Impact Platform, 2024)
The agrifood sector faces a significant climate finance gap, receiving only 0.8 percent of total climate finance. There is an urgent need to increase climate finance. Clear definitions and concessional funding mechanisms are critical for effective financial flows, especially for vulnerable sectors like the agrifood sector. Outcome-based goals for climate finance: The New Collective Quantified Goal (NCQG) must establish outcome-based targets, including for the agrifood sector, reflecting its centrality in Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs).